Design and Experimental Study of a Novel Residential Air Cooled Air-conditioning System for Independent Temperature and Humidity Control (Zhileng xuebao)
Based on the weather conditions in hot and humid area,and present problems of house air-conditioners in this region,a novel residential temperature-humidity independent control air-conditioner was designed to remove the indoor sensible heat load and latent heat load separately,which could enhance the indoor thermal comfort and energy efficiency.The experiments were carried out in the enthalpy difference lab and its SEER(3.932) and the influence of five factors based on orthogonal method,including outdoor ai...